Acute Cytauxzoon felis Cases in Domestic Cats from Eastern Kansas, a Retrospective Case-Control Study (2006–2019) - Yvonne M. Wikander; Qing Kang; Kathryn E. Reif (Veterinary Sciences, 2020)
Cytauxzoon felis, a tick-borne hemoprotozoal pathogen of felids, causes an acute, often-fatal disease in domestic cats. While public awareness of the disease has increased, few studies have evaluated the incidence of acute cytauxzoonosis cases and their associated risk factors. The objective of this study was to retrospectively review records of cats diagnosed with acute cytauxzoonosis in eastern Kansas from 2006–2019 using clinic records and determine: (i) feline cytauxzoonosis risk factors; and (ii) if cytauxzoonosis case incidence is increasing. Although inter-annual variation of acute cytauxzoonosis diagnosis was observed in the eastern Kansas domestic cat population, the overall incidence trend remained largely unchanged over the 14-year case review period. In comparison to ill (C. felis-unrelated) control cases, more acute cytauxzoonosis cases were diagnosed in spring and summer, suggesting a seasonal fluctuation of infection, with samples most commonly submitted from ≥1 year old, owned, male cats. Although cytauxzoonosis case submissions remained consistent over the broad study period, increasing tick vector and domestic cat reservoir populations may contribute to additional cytauxzoonosis case expansion in endemic areas. Investigating the incidence of acute cytauxzoonosis, patient risk factors, and ecological variables that influence disease transmission are important steps towards developing and communicating the need for effective cytauxzoonosis control strategies for high-risk cat populations.